Come to this court & cry : how the Holocaust ends - Kinstler, Linda (PublicAffairs, 2022)
Investigating the death of Herberts Cukurs, a fugitive Nazi from Latvia who had served in her grandfather's unit, and modern efforts to exonerate him for his past actions, the author explores both her family story and the legacy of the post-Holocaust era in Europe, and how that legacy extends into the present.